Pemberdayaan Masyarakat Melalui Pelatihan Tanaman Sayur dalam Pot (TASAPOT) dan Pestisida Nabati (PESNAB) Untuk Meningkatkan Ketahanan Pangan di Desa Sumber Ketempa Kecamatan Kalisat - Sholahuddin Al Ayubi; Angger Dwi Pangestu; Deni Wahyudi; Helmi Muhlisin; Putri Khalishah; Ainun Ingga Iltizamah; Fransiska Ajustina (Al-Khidmah Jurnal Pengabdian Masyarakat, 2025)
Sumber Ketempa Village, Kalisat District, has great potential to develop through natural resource management and agriculture. However, limited land is a challenge for some people in utilizing land for agriculture. To answer this challenge, Collaborative Community Service (KKN) students conducted training on Potted Vegetable Plants (TASAPOT) and the manufacture of Natural Pesticides (PESNAB) with a focus on increasing village food security. This program focuses on cultivating mustard greens in pots that are suitable for people with limited land. In addition, the use of natural pesticides from soursop leaves is taught to maintain plant growth naturally and environmentally friendly. The method begins with licensing, distributing invitations to training activities and introducing the background, benefits, and direct practice of planting vegetable seeds, after the seeds are planted, care is carried out until the seeds are ready to be harvested. This training was attended by villagers, especially housewives, who were invited to practice planting vegetables in pots and making natural pesticides. The results of this activity show that the TASAPOT and PESNAB training are effective in increasing awareness and skills of residents in utilizing limited land to support food security. Thus, this initiative is expected to improve welfare and food independence in Sumber Ketempa Village.